Strategi Pemasaran Produk Tabungan Ib Hijrah Rencana Pada Bank Muamamalat Cabang Manado - Abbas, Afnan I.; Tumbel, Tinneke M.; Kalangi, Johnny A. F (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine the marketing strategy and analyze the strengths, weaknesses, opportunities and threats of the marketing of ibrahim savings products planned by the Bank Muamalat Manado Branch. This research is a descriptive qualitative study with data collection using data using interview and literature studies, while secondary data and primary data from Bank Muamalat employees in Manado Branch. The strategy used by Bank Muamalat Indonesia Branch Manado is to analyze internal and external factors. From the results of this study it can be concluded that the marketing strategy applied is that there are two major factors, namely internal factors and external factors, internal factors using the method of segmentation, targeting, positioning and marketing mix. As well as analyzing external environmental factors such as political, economic, social and technological factors also analyze industrial environments such as newcomers, competition in industry, threats from substitute products and buyers' bargaining power.